Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1016/j.proche.2016.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Hydroxyapatite Reinforced with 45S5 Glass on Physical, Structural and Mechanical Properties

Abstract: This paper presents a study of physical and structural properties of Hydroxyapatite (HA) reinforced with different compositions of 45S5 (SG) bioglasses at different sintering temperatures. Hydroxyapatite reinforced with different compositions of 45S5 bioglasses had been prepared and investigated in terms of density, mechanical strength, and crystalline phases. A decrease in the density of HA was observed after the incorporation of SG, owing to the trapping of air in the SG reinforced HA after sintering process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…In this case, the measured density of ASF glass ceramics was 2.561 g/cm 3 while the density of HA used in this work was 2.673 g/cm 3 . According to a study, the increase in the density of HA-added GIC samples agrees qualitatively with the one, as predicted by the composition relation, and might be due to the replacement of high density of HA powders [ 20 ]. Thus, the density of HA which has a higher density was proposed to dominate the density of cement samples.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…In this case, the measured density of ASF glass ceramics was 2.561 g/cm 3 while the density of HA used in this work was 2.673 g/cm 3 . According to a study, the increase in the density of HA-added GIC samples agrees qualitatively with the one, as predicted by the composition relation, and might be due to the replacement of high density of HA powders [ 20 ]. Thus, the density of HA which has a higher density was proposed to dominate the density of cement samples.…”
Section: Discussionmentioning
confidence: 54%
“…FTIR patterns of GIC and GIC1 samples at different ageing times depicted in Figure 4 revealed the existence of similar spectral bands. The appearance of the spectral band at ~400 cm −1 was belonged to double degenerate O–P–O bending mode (v 2 ) indicated by phosphate group in apatite sample [ 19 , 20 ]. Next, the emergence of triple degenerate O–P–O bending mode (v 4 ) which appeared at both intense peaks at wavenumber ~570 and ~600 cm −1 .…”
Section: Discussionmentioning
confidence: 99%
“…Hydroxyapatite (HA) is a form of calcium phosphate, which is a desirable biomaterial for use. Due to its excellent biocompatibility, HA has been classified as a promising material in many biological applications [4]; however, the low mechanical strength and intrinsic brittleness of HA make it unsuitable as a load-bearing implant fixture and limit its use as a bioactive layer on metal/plastic porous implant materials [5]. Kong et al [6] confirmed that adding some inclusions to ZrO 2 , such as mullite (ZrO 2toughened mullite) and alumina (ZrO 2 -toughened alumina), can improve its mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
“…Calcium phosphate ceramics, which exist in different phases, are the most common materials to be used due to their bioactivity and degradability [1]. Hydroxyapatite (HA) is a member of the calcium phosphate family and has extraordinary properties that make this material compatible with bone tissues and enhance bone growth [2][3][4][5]. HA has been used for many clinical applications, such as bone repair, bone growth, and coating of metallic implants [6].…”
Section: Introductionmentioning
confidence: 99%